An analysis of the structural use of music, song and dance in certain novels by West African writers in relation to concepts of time - Baxter, Marion (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1988)
The topic of this thesis is time in the West African novel in English and French, and the key approach is that West African time is readily grasped through a study of West African music. Though Western time is not exclusively or only linear, mechanical and exploitative, and African time not exclusively cyclic, synchronic and experiential, yet there is a characteristically African view of time and preferred modes of its employment in West African fiction. The novelists considered here wrote in European languages, yet each was a member of a specific cultural group and concerned to portray the aesthetics of his inheritance, an important aspect of which is the predominance of repetitive formulae, both in music and in oral literature. The Introduction offers an historical survey of some of the main notions of time that have been manifest in the West, and compares them with notions of African time. Chapter One examines the structural use of rhythm and repetition in the novels of Camara Laye. Chapter Two discusses the griot and other traditions of oral literature in the novels of Ayi Kwei Armah and Yambo Ouologuem, novels which are concerned with the griot 's continuing role in the creation and dissemination of historical perspective. Chapter Three analyses Chinua Achebe 's portrayal of the values of pre-colonial life in Igbo society where the role of music is to limit behaviour through the structures of ritual which thus create static/cyclic time. Chapter Four describes the syncretic art-form, 'highlife', as used by novelists such as Wole Soyinka, which, because it is transitory and always changing, underscores the ironies of modern city life. The thesis concludes that the authors discussed above are aware that music, because it is predominantly social in Africa, is a powerful medium for achieving a healing synthesis between the traditional past when communalistic values were binding, and the urban-orientated present with its insistence on individuation and material enrichment.
Keywords: Music and literature